Firstly you multiply 5 with everything in the brackets on the left side of = . and than you put t on the left side and change sign (if it was + then its going to be -) and numbers on right side and do the same with signs. then just calculate the rest
5(5t +1) = 25t - 7
25t + 5 = 25t - 7
25t - 25t = -7 + 5
0=-2
the statement is false
Answer:
(x-2) (x^2 -5)
Step-by-step explanation:
x^3 − 2x^2 − 5x + 10
We will factor by grouping
Take and x^2 out of the first two terms and -5 out of the last two terms
x^2 (x-2) -5(x-2)
Now we can factor out (x-2)
(x-2) (x^2 -5)
2x + 3y = 45
x + y = 10......y = 10 - x
2x + 3(10 - x) = 45
2x + 30 - 3x = 45
-x + 30 = 45
-x = 45 - 30
-x = 15
x = -15 <====
and y = 25
Answer: 5x ( x - 5y )
Step-by-step explanation:
ANSWER
![d = - ab + c](https://tex.z-dn.net/?f=d%20%3D%20%20-%20ab%20%2B%20c)
EXPLANATION
The given expression is
![ab = c - d](https://tex.z-dn.net/?f=ab%20%3D%20c%20-%20d)
To find an expression for d in terms of a, b, and c, means we want to make d the subject of the relation.
This means that, we need to isolate d on one side of the equation while all other terms are on the other side.
We subtract from both sides of the equation to obtain,
![ab - c = - d](https://tex.z-dn.net/?f=ab%20-%20c%20%3D%20-%20d)
We now divide through by -1, to get,
![- ab + c = d](https://tex.z-dn.net/?f=%20-%20ab%20%20%2B%20%20c%20%3D%20d)
Or
![d = - ab + c](https://tex.z-dn.net/?f=%20d%20%3D%20-%20ab%20%20%2B%20%20c%20)
The topic is change of subject